Analysis of Phase and Energy Band Gap Width of Corncob Carbon-PEG 4000 - Kusuma Wardhani Mas'udah; Darminto Darminto (Universitas Negeri Malang, 2022)
This study aims to identify and analyze the band gap width of the carbon phase produced from corncobs mixed with PEG-4000 to see the surface area of the corncob carbon phase. First, the characterization test was carried out using Scanning Electron Microscope Energy-Dispersive X-ray (SEM-EDX) spectroscopy to determine the morphology and Ultraviolet–Visible (UV-Vis) spectroscopy to determine the band gap width of corncob carbon. Then, adding Polyethylene Glycol (PEG) 4000 at a specific concentration to develop the potential of corncob carbon. Finally, the corncob-PEG 4000 carbon reduction process was sifted through and tested by UV-Vis spectroscopy, and the energy gap value was 0.954 eV.DOI: 10.17977/um024v7i22022p142